CHA2DS2‐VASc Score as a Predictor for Atrial Fibrillation Recurrence and Clinical Outcomes Following Pulmonary Vein Isolation - Mustafa Gabarin; Mahmoud Suleiman; Adi Elias; Ibrahim Marai; Roy Beinart; Eyal Nof; Yoav Michowitz; Michael Glikson; Yuval Konstantino; Moti Haim; David Luria; David Pereg; et al. (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in adults, associated with serious cardiovascular complications such as ischemic stroke, heart failure, and myocardial infarction. Pulmonary vein isolation (PVI) is an established rhythm‐control strategy for AF. Although the CHA2DS2‐VASc score is primarily used to estimate stroke risk in patients with AF, its potential utility in predicting AF recurrence after PVI has not been fully explored in contemporary, real‐world multicenter settings. Aim To evaluate the association between the CHA2DS2‐VASc score and both AF recurrence and adverse clinical outcomes following PVI. Methods We conducted a retrospective cohort study using the Israeli Catheter Ablation Registry (ICAR), including 860 patients undergoing their first PVI for AF. Patients were grouped by CHA2DS2‐VASc score (0–1, 2–4, > 5). The primary endpoint was AF recurrence within 12 months. Secondary endpoints included re‐hospitalization, major adverse cardiovascular events (MACE), and all‐cause mortality. Results AF recurrence occurred in 32% of patients. Recurrence rates were 25.7%, 31.4%, and 51% across the low, intermediate, and high CHA2DS2‐VASc score groups, respectively. A higher score was independently associated with increased recurrence risk (HR = 2.88; 95% CI, 1.75–4.74; p < 0.001). Elevated CHA2DS2‐VASc scores also correlated with higher MACE and re‐hospitalization rates. No significant difference in all‐cause mortality was observed. Conclusion The CHA2DS2‐VASc score is an independent predictor of AF recurrence and adverse outcomes after PVI. Its simplicity, availability, and routine use make it a clinically useful tool to support preprocedural risk stratification in AF patients undergoing ablation.